Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya pada Mahasiswa PGMI 3 UINSU - Tanjung, Riska Rahman; Wandini, Rora Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to analyze the misconceptions that occur in the operation of working on flat building materials that occur among PGMI 3 Semester 5 students at UIN North Sumatra. The polya theory model is learning that involves students being active, creative, and able to think logistically, critically and at a high level in conveying their ideas to solve mathematical problems they face every day. This research method is a descriptive method used to describe, describe, state a situation, or describe a situation or event to analyze the understanding of polya theory in solving flat shape material problems using an observation approach and test techniques. The subjects in this research were PGMI 3 Semester 5 students of UIN North Sumatra. In solving flat material problems using polya theory which shows the occurrence of misconceptions. This can be seen when students do not write unit signs and symbols because students do not remember and are not careful enough, students do not know the procedures for working on flat shapes using polya theory because students do not understand flat shape materials using polya theory.